STEERing into the Swerve: Adjusting to the Challenges and Opportunities Forced by COVID-19 - Bassett, Roberta (International Higher Education, 2022)
“Drivers” of tertiary education found themselves swerving dangerously and, seemingly, uncontrollably during the pandemic. The action required to regain control over a vehicle when sliding is to steer into the swerve. For higher education leaders around the world, STEERing into the COVID-19 swerve means acknowledging that the crisis pushed tertiary education off its path, resulting in a need for innovative, open-minded thinking to reposition tertiary systems and institutions onto a new one.